The Ridd Case and the model code for the protection of free speech and academic freedom: Wins for academic freedom or losses for university codes of conduct and respectful and courteous behaviour? - Guthrie, Robert; Levine, Pnina (University of Western Australia, 2020)
A successful claim for unlawful dismissal and an award of significant damages and pecuniary penalties in favour of Professor Ridd against James Cook University ('JCU') in the Federal Court has attracted attention in the media and in academic circles. Professor Ridd has been considered by some to be a champion of the rights of academic freedom and free speech at universities. Perhaps less publicized is the Model Code for the Protection of Free Speech and Academic Freedom at Universities ('Model Code') recommended by former High Court Chief Justice Robert French. The Model Code has been seen as a panacea for the protection of these rights, though it has yet to be adopted. A closer examination of the decision in Ridd v James Cook University ('Ridd') and the Model Code reveals both may have unintended consequences for universities. This paper will explore the possibility that Ridd and the adoption of the Model Code may render University Codes of Conduct effectively irrelevant and universities almost powerless when responding to discourteous and disrespectful behaviour by their staff and students.